Quantitative analysis, distribution and traditional management of pigeon pea [Cajanus Cajan (L.) Millsp.] Landraces’ diversity in Southern Benin - Zavinon, F.; Adoukonou-Sagbadja, Hubert; Ahoton, L.; Vodouhe, R.S.; Ahanhanzo, C. (Euroepan Scientific Institute, 2018)
Pigeon pea (Cajanus cajan (L.) Millsp.) is an important drought tolerant legume cultivated in the semi-arid regions, mainly in Sub-Saharan Africa. Despites its important potential, the crop is neglected and underutilized in many countries including Benin. In order to develop efficient in-situ strategies conservation, a study was conducted to quantify pigeon pea landrace diversity and access its spatial distribution and traditional management by local communities in southern Benin. Therefore, an ethnobotanical survey was conducted in 20 producing villages in southern Benin. Altogether, 26 farmernamed landraces further grouped into five categories were recorded with the number of landraces really cultivated per farmer comparably lower than that listed. Besides, two landraces’ categories were found to be common in the study area while two other were found highly threatened. Diverse parameters such as varietal richness, Shannon-Weaver Diversity Index, Simpson index and Pielou’s evenness were used to quantify pigeon pea diversity that appeared to be unequally distributed through the different agro-ecologies and villages surveyed. The study confirmed the absence of correlations between farmers’ gender and landrace diversity which was nonetheless found to be significantly shaped by the ethnic group and the field size exploited by farmers (P < 0.05). In diversity management, five preference criteria with variable importance across the ethnic groups were used by farmers of which cooking time and market value appeared to be the most important. Exhaustive germplasm collections, morphological/molecular characterizations of these landraces are required for efficient conservation of this important but neglected crop genetic resource in Benin.